Rhabdomyolysis in hepatitis A: Uncommon complication of a common infection - M Suresh Babu; H G Ashoka; Anusri Adusumilli (Wolters Kluwer Medknow Publications, 2023)
Hepatitis A is usually a mild self-limiting infection of liver. Rhabdomyolysis complicating acute nonfulminant hepatitis A is exceedingly rare. We present here a case report of 19-year-old young male with hepatitis A, who developed rhabdomyolysis with acute renal failure. He underwent dialysis and made a complete recovery with normalization of laboratory tests.